log(6x-5)+log(x+5)=1

Simple and best practice solution for log(6x-5)+log(x+5)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(6x-5)+log(x+5)=1 equation:


Simplifying
log(6x + -5) + log(x + 5) = 1

Reorder the terms:
glo(-5 + 6x) + log(x + 5) = 1
(-5 * glo + 6x * glo) + log(x + 5) = 1
(-5glo + 6glox) + log(x + 5) = 1

Reorder the terms:
-5glo + 6glox + glo(5 + x) = 1
-5glo + 6glox + (5 * glo + x * glo) = 1
-5glo + 6glox + (5glo + glox) = 1

Reorder the terms:
-5glo + 5glo + 6glox + glox = 1

Combine like terms: -5glo + 5glo = 0
0 + 6glox + glox = 1
6glox + glox = 1

Combine like terms: 6glox + glox = 7glox
7glox = 1

Solving
7glox = 1

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '7lox'.
g = 0.1428571429l-1o-1x-1

Simplifying
g = 0.1428571429l-1o-1x-1

See similar equations:

| 96=17x-5x | | 2x^2+5x+9=0 | | 9u+8/5+5u+5/4=12 | | 10x^2+25x+45=0 | | 3x+2x+4x=15+8 | | -5(a-2b+3a-2b)=2(-2-3b) | | 0=9x+3 | | 3y^2-10y+7=0 | | 9q+15q= | | =.2x^2-2.4x+.2 | | 6(k-3)-5(k+2)= | | =2x^2-4x+9 | | 250+125x+x^2=1250 | | 3*x^2+8*x+4=0 | | 7y^2-34y-5=0 | | 2x+5x-3x+4=3x | | 7y^2+13y-2=0 | | =2x^2+16x-2 | | 4x^2-21x-49=0 | | 4x+5+2x=7x | | 4x-21x-49=0 | | .25(x-8)=6 | | 13-3x=-6x+16 | | 5y-1+5y=4 | | 255=(-2x)(.147-x)(.18-x) | | 2x+3x=32 | | 3x^2-67x=-6x^2-5x-48 | | =-2x^2-28x-96 | | 3x^2-10x+25=0 | | -4m+8=-3m+1 | | .5(x-6)=4 | | X^3-64y^3= |

Equations solver categories